Multibeam bathymetry raw data (Wärtsilä ELAC 3050 entire dataset) of RV POSEIDON during cruise POS500 - Fleischmann, Timo; Kopf, Achim J (PANGAEA, 2025)
Raw bathymetry data were collected using the ship's own SeaBeam 3050 multibeam echosounder during the RV POSEIDON cruise POS500 Ligurian Slope AUV mapping, gravity coring and seismic reflection (LISA). The cruise took place between 2016-05-25 and 2016-06-09 (Catania, Italy - Malaga, Spain), aiming to investigate the controls of slope failure and submarine landslide processes off the Nice International Airport focusing on the 1979 landslide and resulting tsunami. The ship's echosounder data were complemented by the bathymetry data collected by the AUV SEAL, multi-channel seismic survey and gravity coring. No sound velocity profiles (SVP) were collected during the cruise. Data are unprocessed and contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).
Keywords: Bathymetry; Multibeam Echosounder